(untitled) (CIPEEX, 2025)
This research aims to address the challenges related to the means of combating illicit drug trafficking in the state of Goiás, when it comes to the diversity of psychotropic drugs, considering that marijuana, also known as cannabis stativa, is the most consumed drug in the Brazil. Through bibliographical review and data analysis from the Public Security Secretariat of the State of Goiás, it was possible to demonstrate information about the history of illicit drug trafficking, as well as the concept and distinction between trafficking and personal consumption. The results obtained demonstrate the strategies to combat illicit drug trafficking, through police operations with the aim of combating the trade in illicit drugs, an extremely effective method, as well as the socio-educational projects promoted by the State of Goiás. It was also proven that the serious damage that drug trafficking causes to society, as well as the impact on the health system and the increase in crime.